Faktor Risiko Hipertensi pada Wanita Pekerja dengan Peran Ganda Kabupaten Bantul Tahun 2011 - Elvyrah Faisal, Bambang Djarwoto, Berty Murtiningsih (Berita Kedokteran Masyarakat (BKM), 2012)
Background: Hypertension or high blood pressure is lethal disorder that can be found in the people at developed countries and developing countries. The prevalence of hypertension in Yogyakarta Special Region based on the result of blood pressure measurement was 28.4%, the prevalence of hypertension in Bantul Regency based on the result of blood pressure measurement was 23.9%. The morbidity of hypertension for 2006 to 2010 experienced significant increasing. The prevalence of hypertension in female was higher compared in male and tends to increase each year.Objectives: To knowing the risk factors of hypertension in the worker female with double role in Bantul Regency in 2011.Methods: This was observational analytic study by case control design, the subject of the study was the worker woman that meet inclusion criterion and the one that meet exclusion criterion was excluded. The number of subject was 216. Analysis was performed used Mc Nemar test with significance level at 95%, and then was followed by conditional logistic regression analysis to knowing the dominant factors of the hypertension incidence.Results: The result of the study showed that the variable of physical activity (OR= 5.69, 95%CI= 2.248-14.448), psychosocial stress (OR= 3.28, 95%CI= 1.051-10.263), obesity (OR= 2.78, 95%CI= 1.061-7.331), family history (OR= 2.19, 95%CI= 1.051-4.587), education (OR= 4.62, 95%CI= 1.624-13.161), contraception usage (OR= 3.99, 95%CI= 1.159-13.763) were risk factors for hypertension incidence in the worker woman with double role in Bantul Regency.Conclusion: The risk factors of hypertension incidence in the worker woman with double role were physical activity, psychosocial stress, obesity, family history. Work load was not risk factors for hypertension incidence in the worker woman with double role in Bantul Regency.Keywords: risk factors, hypertension, worker woman with double role